DIVERSITY, ROLE AND THREATS TO THE SURVIVAL OF BATS IN PAKISTAN - M. Mahmood-ul-Hassan; P.O. Nameer (Journal of Animal and Plant Sciences, 2006)
Bats are among the least studied group of mammals in Pakistan. We reviewed and compared the diversity of bat fauna of Pakistan with that of the world, the Palearctic region and the Indo-Malayan region and found that the bat diversity of the country is comparable to any other region of the world with similar climatic conditions. Eight families of order Chiroptera with 23 genera (11.5%) are represented within a short geographic area of Pakistan in comparison to the Palearctic (13%) and the Malayan regions (18.5%) where 26 and 37 bat genera are present, respectively. The country therefore deserves to be designated as a hotspot for conservation of bat biodiversity and measures should be taken to conserve it as public awareness about the significance of biodiversity is low.
Keywords: Batso conservation; Indo-Malayan; Pakistan; Palearctic